2019
DOI: 10.3390/ijms20020404
|View full text |Cite
|
Sign up to set email alerts
|

The Role of O-GlcNAcylation for Protection against Ischemia-Reperfusion Injury

Abstract: Ischemia reperfusion injury (IR injury) associated with ischemic heart disease contributes significantly to morbidity and mortality. O-linked β-N-acetylglucosamine (O-GlcNAc) is a dynamic posttranslational modification that plays an important role in numerous biological processes, both in normal cell functions and disease. O-GlcNAc increases in response to stress. This increase mediates stress tolerance and cell survival, and is protective. Increasing O-GlcNAc is protective against IR injury. Experimental cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 143 publications
3
27
0
Order By: Relevance
“…[45][46][47] However, other studies reported that O-GlcNAcylation of Akt positively modulates Akt activity. [48][49][50][51] In the present study, we found that Akt and mTOR are O-GlcNAcylated proteins in hepatoma cells. Akt/mTOR signaling pathway is known to negatively regulate HBV replication.…”
Section: Discussionsupporting
confidence: 61%
“…[45][46][47] However, other studies reported that O-GlcNAcylation of Akt positively modulates Akt activity. [48][49][50][51] In the present study, we found that Akt and mTOR are O-GlcNAcylated proteins in hepatoma cells. Akt/mTOR signaling pathway is known to negatively regulate HBV replication.…”
Section: Discussionsupporting
confidence: 61%
“…Uridine diphosphate-N-acetylglucosamine (UDP-GlcNAc) is produced and used as the substrate of O-linked-GlcNAc transferase (OGT), which catalyzes the O-GlcNAcylation (O-GlcNAc) of proteins (48). Protein O-GlcNAcylation plays an essential role as a protective response in cardiomyocyte senescence via reducing calcium overload, mitochondrial permeability transition pore opening, ER stress, modification of inflammatory and heat shock responses (49). Of note, the cardiac protective effects of increasing O-GlcNAc levels have been emphasized in many pathologic conditions, including ischemic injury (50,51).…”
Section: The Regulation Of Metabolism Dysfunction On Cardiomyocyte Sementioning
confidence: 99%
“…Experimental cardiac ischaemia/ reperfusion models showed that acute increases in protein O-GlcNAcylation induced by GlcN or glutamine correlated with a better functional recovery, while similar conclusions were obtained with the more clinically applicable remote ischaemic preconditioning. 29 In contrast to the benefit in acute and transient elevations, chronic increments or decreases in the levels of O-GlcNAcylated proteins have been associated with the pathogenesis of degenerative diseases such as Alzheimer's and Parkinson's, cancer, diabetes and Glucose enters the cell and is phosphorylated and then converted to fructose-6-phosphate. This product is then oxidised through glycolysis, and 3%-5% of it is converted to glucosamine-6-phosphate (GlcN-6P) by the limiting enzyme of this pathway, glutamine:fructose-6-phosphate-amidotransferase (GFAT), that transfers the amine group from the amino acid pool.…”
Section: Glucosamine and O-glcnacylation: A Novel Immunometabolic Thementioning
confidence: 99%